Increasing Students’ Ability In Writing Skill Of Descriptive Text By Using Facebook - Muhammad Farizul Umam (Rahis Cendekia Indonesia, 2023)
Writing is one among the critical abilities learned in English. In writing, individuals express their thoughts and conclusions. In this period of progressed communication innovation, the utilize of social media to instruct and help understudies to memorize is common for teachers. This investigate explored the adequacy of utilizing Facebook in educating writing of expressive writings. As pre-experimental inquire about, this inquire about utilized composed tests of descriptive writings as the most instrument and meet as the supplementary information collection strategy. The tests of this investigate were eleventh review understudies of Social one of a open senior tall school. The result of this inquire about appeared that there was a noteworthy contrast on the students' capacity of writing expressive writings some time recently and after the treatment. The meet reactions too demonstrated that utilizing Facebook post as visual media for learning expressive was successful. In conclusion Facebook posts as visual media in instructing clear writings can progress student's writing capacity of expressive content.